شركة قناة السويس للاستزراع السمكى والأحياء المائية - Hassan, Albassel A. (2018)
As part of the IFPRI Egypt Seminar in partnership with WorldFish: “Leveraging Aquaculture and Fisheries for Improving Food and Nutrition Security in Egypt”